Frequency upconversion in Er3+ doped Y2O3 nanophosphor:Yb3+ sensitization and tailoring effect of Li + ion - Mishra K.; Singh S.K.; Singh A.K.; Rai S.B. (My University, 2025)
Er3+ doped Y2O3 nanophosphor has been synthesized using solution combustion technique and further characterized for structure and optical properties. Optical properties of Er3+ ion have been studied both through frequency upconversion (UC) as well as through fluorescence (excitation, emission, and CIE co-ordinate analysis) processes. Further to enhance the UC emission of Er3+ ions, a two step process has been used. In the first step, Yb3+ ion has been co-doped, which acts as the sensitizer for Er3+ through energy transfer process. In the second step, different concentrations of Li+ ions have been co-doped in the Er3+/Yb3+:Y2O3 system. Fourier transform infrared analysis, and X-ray diffraction (XRD) followed by Le-Bail refinement of the XRD data reveal that the co-doping of Li+ ion decreases unit cell parameter, increases the particle size, and removes the quenching centers (like OH, NOx, etc.), which all together causes a significant enhancement in UC emission. Optimum UC luminescence is attained for 5 mol% Li+ doping concentration beyond which a quenching in UC emission is observed. This combined approach, i.e. Yb3+ sensitization and Li+ ion tailoring simultaneously enhances the UC emission intensity of Er3+ several times in yttria matrix effectively. The strategy can be generalized in other hosts also which could help in the development of efficient photonic materials for lighting and display devices. © 2013 Elsevier Ltd. All rights reserved.